The category of sacrum in the artistic universe created by Valeriy Schevchuk (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article examines functioning  of the image of God in the artistic world created by Valeriy Schevchuk. It pays special attention to a variety of  God’s hypostases: the Creator of Entity, the Creator of  God’s logos, God as Love, the Lord of Paradise. A sacred image structures the wholeness of the intertext.
Keywords: sacrum; author; text; modus; time; space